2021
DOI: 10.1029/2021gc009987
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Stress Localization Caused by Lithospheric Heterogeneity From Seismic Attenuation

Abstract: Cratons, the cores of continents, typically resist tectonic deformation and are generally devoid of contemporary seismic and magmatic activity (e.g., Lee et al., 2011). Nevertheless, geophysical and geological observations indicate that cratons can be subject to the destructive effects of tectonic and mantle dynamics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 85 publications
(162 reference statements)
2
7
0
Order By: Relevance
“…This is consistent with empirical findings from previous studies that have shown that the anticorrelation between velocity structure and attenuation is strongest at depths of 100-200 km (J. S. Byrnes et al, 2019;H. Liu et al, 2022;Zhu et al, 2021). A correction for physical dispersion due to anelasticity is not made, but would not significantly change the results given the relevant periods (J.…”
Section: Whole Study Areasupporting
confidence: 91%
See 4 more Smart Citations
“…This is consistent with empirical findings from previous studies that have shown that the anticorrelation between velocity structure and attenuation is strongest at depths of 100-200 km (J. S. Byrnes et al, 2019;H. Liu et al, 2022;Zhu et al, 2021). A correction for physical dispersion due to anelasticity is not made, but would not significantly change the results given the relevant periods (J.…”
Section: Whole Study Areasupporting
confidence: 91%
“…We apply attenuation measurement and imaging techniques that have been successfully used recently in different settings (Bezada, 2017; Bezada & Smale, 2019; J. S. Byrnes & Bezada, 2020; J. S. Byrnes et al., 2019; Deng et al., 2021; Zhu et al., 2021). We measure t * in the time domain by numerically attenuating an estimate of the source time function to match the observed waveforms.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations